2017
DOI: 10.1016/j.rmed.2017.03.015
|View full text |Cite
|
Sign up to set email alerts
|

Long-term safety and efficacy of glycopyrrolate/formoterol metered dose inhaler using novel Co-Suspension™ Delivery Technology in patients with chronic obstructive pulmonary disease

Abstract: Results confirmed the long-term safety and tolerability of GFF MDI 18/9.6 μg twice-daily in subjects with moderate-to-very severe COPD. Improvements in efficacy endpoints were also sustained over 52 weeks.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
68
0
12

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 66 publications
(87 citation statements)
references
References 40 publications
7
68
0
12
Order By: Relevance
“…The improvements in IC were consistent with two 4-week studies of GFF MDI in patients with moderate-to-very severe COPD (248–381 mL peak change from baseline in IC) and a 7-day study of higher doses of GFF MDI (GFF MDI 72/9.6 μg and 36/9.6 μg; 265–293 mL peak change from baseline in IC) 13,14. GFF MDI treatment amounted to a decrease of approximately half a liter in FRC and RV vs placebo MDI (13% and 22%, respectively), which is consistent with the reduction in FRI airway resistance observed and implies a reduction in air trapping and hyperinflation.…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…The improvements in IC were consistent with two 4-week studies of GFF MDI in patients with moderate-to-very severe COPD (248–381 mL peak change from baseline in IC) and a 7-day study of higher doses of GFF MDI (GFF MDI 72/9.6 μg and 36/9.6 μg; 265–293 mL peak change from baseline in IC) 13,14. GFF MDI treatment amounted to a decrease of approximately half a liter in FRC and RV vs placebo MDI (13% and 22%, respectively), which is consistent with the reduction in FRI airway resistance observed and implies a reduction in air trapping and hyperinflation.…”
Section: Discussionsupporting
confidence: 83%
“…Despite the relatively small population, the study was well powered, and the size is not unusual for a study of this type 1,2,5. The 14-day study duration ensured that steady-state pharmacokinetics were achieved for glycopyrrolate and formoterol 11,13…”
Section: Discussionmentioning
confidence: 99%
“…Of note, another study showed no significant difference compared to TIO [34]. IND/GLY was superior to SAL/FLU 50/500 in the study of Wedzicha et al [28] enrolling COPD patients with mMRC > 2 and FEV 1 25-60% predicted but not in the studies performed by Vogelmeier et al [33] and Zhong et al [29] including, respectively, COPD patients stages 2-3 according GOLD 2009 and stages 2-3 GOLD 2010 and MRC ≥2. The percentage of patients who reached the MID with GLY/ IND was significantly higher compared to that of the placebo [30], GLY [30,36], SAL/FLU 50/500 [28] or TIO [31].…”
Section: Resultsmentioning
confidence: 91%
“…One study used the only the CAT to assess HRQoL [18], while the St George's Respiratory Questionnaire (SGRQ) [19][20][21] was used in 27 RCTs . Three RCTs [23,29,37] also used the COPD Assessment Test (CAT) [43][44][45], and 2 papers [38,39] used the EQ-5D [46,47]. Table 1 reports the characteristics of the tools that were used in the selected RCTs.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation